Intrusion Detection in Distributed Systems An Abstraction-Based Approach - Peng Ning; Jajodia, Sushil; Wang, Xiaoyang Sean (Advances in Information Security, 2004)
Intrusion Detection In Distributed Systems: An Abstraction-Based Approach presents research contributions in three areas with respect to intrusion detection in distributed systems. The first contribution is an abstraction-based approach to addressing heterogeneity and autonomy of distributed environments. The second contribution is a formal framework for modeling requests among cooperative IDSs and its application to Common Intrusion Detection Framework (CIDF). The third contribution is a novel approach to coordinating different IDSs for distributed event correlation